Human immunodeficiency virus/human parvovirus B19 co-infection in blood donors and AIDS patients in Sichuan, China - He, Miao (Edizioni SIMTI — SIMTI Servizi Srl, 2012)
BACKGROUND: Human parvovirus B19 (B19) is a common pathogen which causes a variety of diseases. Persistent B19 infection is related to the degree of host immunodeficiency in patients with human immunodeficiency virus (HIV) infection. However, the existence, loading, virus evolution and distribution of B19 in Chinese HIV-positive patients have not been determined. MATERIALS AND METHODS. We investigated 573 HIV-positive blood donors and AIDS patients in Sichuan, China in the last two decades. Bl9-specific serology and quantitative polymerase chain reaction were used to determine the prevalence of B19/HIV co-infection. Viral genome fragments were subjected to phylogeny and haplotype analysis. RESULTS: B19 genomic DNA was found in 26 of 573 (4.5%) HIV-positive individuals, a higher prevalence than in blood donors. DNA levels ranged from 5.3×10(2)–1.1×10(5) copies/mL. The seroprevalence of IgG was significantly lower in HIV-positive samples than in HIV-negative blood donors, indicating deficient production of B19-specific IgG in the former. The B19 isolates were genotype-1 subtype B19-1A which formed a monophyletic group; seven distinct haplotypes were discovered with 60% of the B19/HIV co-infected variants sharing one central haplotype. DISCUSSION. This study on the prevalence, phylogeny and distribution of human parvovirus B19 in Sichuan, China, demonstrates the persistence of B19 in the circulation of both immunocompetent and immunocompromised subjects, with implications for blood safety.